Aktivitas antibakteri propolis madu putih sumbawa terhadap pertumbuhan Staphylococcus epidermidis, Staphylococcus aureus dan Escherichia coli - Wardoyo, Eustachius Hagni; Rosyunita; Rahim, Adelia Riezka; Arnawati, Ida Ayu; Haza, Saskia Safarina; Hulfifa, Lale Nandhita; Alamsyah, Abiel Dwi Cahya Firdaus; Validika, I Komang Satya; Hasbi, Nurmi (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
Silent pandemic is a health issue related to antimicrobial resistance. Currently, deaths due to antimicrobial resistance in the world reach 700 thousand people per year and it is predicted that by 2050 it could reach 10 million people. So exploring new alternative sources is a must. One ingredient that is often used as an infection medicine and health supplement is honey propolis. Sumbawa white honey propolis is a biological product that has not yet been widely explored for its potential as an antibacterial. The research aims to determine the phytochemical content and antibacterial potential of Sumbawa white honey propolis against Staphylococcus epidermidis, Staphylococcus aureus and Escherchia coli. This research is a true experiment research with a post-test only control group design. Propolis is extracted by maceration with propylene glycol as a solvent. The concentrations of propolis extract used are 100%, 75% and 50%. Chloramphenicol positive control and 10% DMSO negative control. The antibacterial test was detected in five replications on Mueller Hinton Agar media using the disk diffusion method by measuring the diameter of the inhibition zone. Data were analyzed statistically using the OneWay Anova test. Sumbawa white honey propolis contains flavonoids, tannins and triterpenoids. The results showed that propolis was unable to inhibit gram-negative E. coli bacteria with an inhibition zone diameter of 0 mm. Different results in gram positives, Sumbawa white honey propolis was able to inhibit the growth of S. epidermidis and S. aureus. The results showed that propolis was unable to inhibit gram-negative E. coli bacteria with an inhibition zone diameter of 0 mm. Different results in gram positives, Sumbawa white honey propolis was able to inhibit the growth of S. epidermidis and S. aureus. However, Sumbawa white honey propolis against both gram-positive bacteria was in the weak category compared to the positive control. This is because all the Sumbawa white honey propolis concentration series have an inhibitory zone diameter of ≤ 5 mm.